Assessment of the Impairment in Domain functionalities and Executive Functions in Euthymic Patients, with Bipolar Disorder I/II - Utilizing the FAST and FAB tests - Cyrino, Luiz Arthur Rangel; Calegari, Claudia Regina; Tomasi, Maria Cecília; Stammerjohann, Felipe Luis Schmoller; Lima, Daniela Delwing-de (International Journal of Advanced Engineering Research and Science, 2021)
Objective: In this article, we focus on assessing two key predictors of outcomes in Bipolar Disorder (BD): cognition and functionality performance, and researching for a correlation between them. Methods: Subjects were patients with BD in the euthymic phase (n=50), and healthy controls (n=25). Psychosocial functioning was evaluated using the Functioning Assessment Short Test (FAST), and the same group underwent the Frontal Assessment Battery (FAB) to assess the Executive Functions (EF). Clinical and sociodemographic characteristics were analyzed using one-way analysis of variance or the chi-square test. To verify a correlation between FAB and FAST tests, we used the Spearman Correlation Coefficient. Results: Patients with BD showed higher FAST total scores (24.60±11.09) than healthy controls (9.80±5.94) (p< 0.001), and patients with BD showed lower FAB total scores (13.56±2.81) than healthy control (15.72±1.64) (p<0.001). Associated with these results, bipolar patients showed higher FAST scores in all domains predominantly with moderate impairment (score 21-40), and also lower scores in the following three domains: conceptualization, sensitivity to interference, and inhibitory control in the FAST test (p<0.05). The correlation between the variables FAB and FAST presented a moderate intensity (r2= -0.539). Conclusion: This study reinforced the impact of BD in functionality and the EF, demonstrating alterations in several domains: social, occupational, and cognitive functions impairment. Understanding them is crucial for these patients, which increases the possibility of rehabilitation and the response to treatment.